Pengaruh Manajemen Pengetahuan, Keterampilan dan Sikap terhadap Kinerja Karyawan - Abdul Latief; Nurlina Nurlina; Eko Medagri; Agung Suharyanto (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2019)
The purpose of this study was to determine the effect of Knowledge, Skills and Attitudes Management simultaneously and partially on the Employee Performance of PT. Langsa Plantation Nusantara I. This research was conducted at the Head Office of PT. Langsa Perkebunan Nusantara I, the study was conducted for two months. 83 employees were surveyed randomly as respondents. The data analysis method used is multiple linear regression analysis. From the data analysis obtained the regression equation Y = 1,042 + 0,132X1 + 0,220X2 + 0,391X3. Furthermore, from the results of the analysis it is known that the value of t arithmetic is 1.665> t table 1.664 and the value of t sig. 0.041 <0.05, which means that the Knowledge Management variable influences employee performance variables. While for the Skill variable, the value of t arithmetic is 2.267> t table 1.664 and the value of t sig. 0.026 <0.05 which means that the Skill variable has a significant effect on employee performance variables. And for the Attitude variable obtained t count value of 4.335> t table 1.664 and t value sig. 0.00 <0.05 which means that the attitude variable has a significant effect on employee performance variables. Knowledge, Skills and Attitudes Management simultaneously has a significant effect on employee performance at the Head Office of PT. Langsa Perkebuanan Nusantara I where F count value is 25,477> 3,29.